Fluorescent probes for nanoscopy: four categories and multiple possibilities. Issue 1 (25th May 2016) - Ni, Ming; Zhuo, Shuangmu; So, Peter T. C.; Yu, Hanry
Abstract : Nanoscopy enables breaking down the light diffraction limit and reveals the nanostructures of objects being studied using light. In 2014, three scientists pioneered the development of nanoscopy and won the Nobel Prize in Chemistry. This recognized the achievement of the past twenty years in the field of nanoscopy. However, fluorescent probes used in the field of nanoscopy are still numbered. Here, we review the currently available four categories of probes and existing methods to improve the performance of probes. Abstract : Nanoscopy enables breaking down the light diffraction limit and reveals the nanostructures of objects being studied using light. In 2014, three scientists pioneered the development of nanoscopy and won the Nobel Prize in Chemistry. This recognized the achievement of the past twenty years in the field of nanoscopy. However, fluorescent probes used in the field of nanoscopy are still numbered. Here, we review the currently available four categories of probes and existing methods to improve the performance of probes.Four categories of fluorescent probes used for nanoscopy.